Fundamentals of management text and Philippine cases - Rodriguez, Rafael A.; Echanis, Erlinda S. (Mandaluyong City Diwata Publishing, 1997)
The changes in the third edition involve the updating of examples and illustrations, as well as data in various tables in Chapter 3. A section on business reengineering and on new control measures were added in Chapter 8 and 15, respectively, to cover two management issues which have received considerable attention in the business literature in recent years.

Seven new cases were also added to broaden the selection from which the teacher can choose. The new cases are
1. Rural Bank of Suares (Issues in Planning)
2. Peso Bank (Issues in Organizing)
3. Gintong Hiyas (Reward and Compensation Systems)
4. Super-Lab, Inc. (Reward and Compensation Systems)
5. First National Bank (Directing)
6. The ATM in UP Diliman (Directing)
7. C-5 Milling Corporation (Control Tools and Techniques)
Part I: Introduction
Chapter 1: Managers and development
Chapter 2: Origins of contemporary management thought
Chapter 3: The firm and its environment
Chapter 4: Forms of business organizations in the Philippines

Part II: The Management Process
Chapter 5: Planning
Chapter 6: Issues in planning
Chapter 7: Organizing
Chapter 8: Issues in organizing
Chapter 9: Staffing
Chapter 10: Reward and compensation systems
Chapter 11: Directing
Chapter 12: Theories of leadership
Chapter 13: Control
Chapter 14: Control tools and techniques
Chapter 15: Issues in control
Includes index.
Includes bibliographical references and index.
Includes bibliographical references
Keywords: Management -- Philippines